Allometric scale model reveals temperature effects on growth and reproduction in Daphnia magna - Hideyasu Shimadzu; Miguel Barbosa (Scientific Reports)
Abstract Climate change amplifies temperature variability, thereby subjecting organisms to increased stress as they more frequently encounter temperatures outside their optimal range. Temperature influences resource distribution across fundamental processes in organisms, such as metabolism, reproduction and overall fitness, yet energy allocation strategies are primarily understood under stable temperature conditions. Predicting organisms’ responses to fluctuating temperatures, however, remains challenging. To address this gap, we develop an allometric growth model to predict energy allocation between growth and reproduction under both constant and variable temperature conditions. The model predictions perform and align well with the observed growth patterns of Daphnia magna, a keystone species in aquatic ecosystems, exposed to various thermal scenarios. Results indicate that exposure to unpredictable temperatures elicits growth and reproduction responses similar to those observed under consistently high temperatures. However, individuals exposed to unpredictable temperatures incur a disproportionate energetic cost compared to those in constant average or low-temperature conditions, significantly reducing estimated fecundity over time and lifespan. These findings highlight the relative energetic impacts of increased unpredictability in temperature and underline its critical role in shaping life-history traits. Given the growing concern over modern climate change scenarios, the allometric growth model provides a straightforward yet essential approach for integrating energetic and subsequent ecological effects, enabling not only predictions of responses across keystone species but also an enhanced understanding of anthropogenic impacts on aquatic ecosystems.